Vacuum-stent: A combination of endoscopic vacuum therapy and an intraluminal stent for treatment of esophageal transmural defects - Pattynama, Lisanne M. D.; Eshuis, Wietse J.; van Berge Henegouwen, Mark I.; Bergman, Jacques J. G. H. M.; Pouw, Roos E. (Frontiers in Surgery, 2023)
Introduction: Endoscopic vacuum therapy (EVT) has gained a greater role in management of transmural defects in the upper gastrointestinal (GI) tract, including anastomotic leakage and esophageal perforation (e.g. Boerhaave syndrome, iatrogenic cause). The vacuum-stent is a new treatment modality, combining the benefits of EVT and an intraluminal stent. Patients and methods: This prospective case series describes the first ten cases of a transmural defect in the upper GI tract treated with a vacuum-stent in a tertiary referral center. All patients signed informed consent for prospective registration of relevant data on treatment and outcomes in a specially designed database. Outcome parameters were successful closure of the defect, number of endoscopies, duration of treatment and adverse events. Results: In total, ten patients treated with a vacuum-stent were included. Eight patients had anastomotic leakage, of whom six were treated with vacuum-sponge and vacuum-stent, and two with vacuum-stent only. One patient had Boerhaave syndrome, treated with vacuum-sponge and vacuum-stent, and one had an iatrogenic perforation during pneumodilation for achalasia, treated with vacuum-stent only. Success rate was 100%, requiring a median of 5 (IQR 3-12) EVT-related endoscopies with a treatment course of median 18 (IQR 12-59) days. One patient developed an esophageal stricture, but no other vacuum-stent related adverse events were observed. Conclusion: The vacuum-stent, which combines benefits of EVT and an intraluminal stent, shows great feasibility and efficacy in treatment of transmural defects in the upper GI tract. Future studies should point out whether this device can prevent major (re-)surgery in these patients.